La enseñanza de estrategias metacognitivas para el mejoramiento de la comprensión lectora. Estado de la cuestión - Aragón Espinosa, Lucero (2022)
This paper describes a review of studies on teaching metacognitive strategies for improving reading comprehension. Research reports and theoretical essays published between 1996 and 2008 were analyzed and organized in a matrix, which permitted the classification of the variables tackled in the studies. The results of the studies show a significant improvement in reading comprehension, after the students participated in instruction programs. The conclusions lead to some general and specific guidelines that could be taken into consideration by people working in the design, implementation and evaluation of prevention and intervention programs, with the aim of improving students’ reading comprehension.